2011
DOI: 10.1007/s00231-011-0936-z
|View full text |Cite
|
Sign up to set email alerts
|

Influence of coolant injector configuration on film cooling effectiveness for gaseous and liquid film coolants

Abstract: An experimental investigation is conducted to bring out the effects of coolant injector configuration on film cooling effectiveness, film cooled length and film uniformity associated with gaseous and liquid coolants. A series of measurements are performed using hot air as the core gas and gaseous nitrogen and water as the film coolants in a cylindrical test section simulating a thrust chamber. Straight and compound angle injection at two different configurations of 30°-10°and 45°-10°are investigated for the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Shine et al [12] investigated the effects of different coolant configuration as the length of cooling holes and the uniformity of film cooling depend on the liquid or gaseous coolants on cooling performance. The results declared that at low blowing ratios, there was no difference between the effects of different coolant on cooling.…”
Section: Methodsmentioning
confidence: 99%
“…Shine et al [12] investigated the effects of different coolant configuration as the length of cooling holes and the uniformity of film cooling depend on the liquid or gaseous coolants on cooling performance. The results declared that at low blowing ratios, there was no difference between the effects of different coolant on cooling.…”
Section: Methodsmentioning
confidence: 99%
“…The validation of test cases is based on the measurements made using the similar experimental setup used by Shine et al [29] and is shown in Fig. 1.…”
Section: Experiments Used For Validationmentioning
confidence: 99%
“…The temperature of the mainstream hot air remained almost constant over the entire test section length. A brief description of the various uncertainties present in the experiment is explained in [29]. The relative uncertainty in the deduced parameters has been estimated using the method due to Moffat [30].…”
Section: Experiments Used For Validationmentioning
confidence: 99%
“…An effective cooling of the nozzle is very crucial for ensuring reliability of the rocket engines developed for space missions. However, very few studies deal with coolant film injector orientations and its effect on film cooling effectiveness [6]. In this study, experimental and computational results are presented that describe film cooling effectiveness of a nozzle segment having two types of coolant injector orientations.…”
Section: Introductionmentioning
confidence: 99%